On the eigenvalues and eigenvectors of nonsymmetric saddle point matrices preconditioned by block triangular matrices - Pestana, J (2013)
Block lower triangular and block upper triangular matrices are popular preconditioners for nonsymmetric saddle point matrices. In this note we show that a block lower triangular preconditioner gives the same spectrum as a block upper triangular preconditioner and that the eigenvectors of the two preconditioned systems are related.